Applying the positioning phase of the digital transformation model in practice for SMEs: toward systematic development of digitalization - Kääriäinen, Jukka (2021)
Digital transformation (DT) refers to the changes in ways of working and business offering caused by adoption of digital technologies in an organization. Small and medium-sized enterprises (SMEs) are struggling with this transformation because of their limited resources and know-how. Thus, SMEs need practical grassroots-level help for DT that allows the companies to analyze where they stand in digitalization, and how they should proceed. This article discusses how SMEs can be supported in their DT by utilizing the DT model consisting of four consecutive phases for supporting companies’ systematic development of digitalization. The article focuses on the first phase of the DT model, positioning, where company’s digitalization status is analyzed in detail, and development ideas are identified. The positioning phase was conducted for 19 SMEs in Northern Ostrobothnia, Finland. The results indicate that the used process and tools were suitable to support SMEs for analyzing their digitalization status and identifying areas for improvement. The DT model and piloted tools have been published as a free-of-charge ApuaDigiin.fi online service to facilitate their widespread use in the future. In this way, public regional business development authors or research organizations can utilize the online service while supporting the digitalization of SMEs.